2013
DOI: 10.1118/1.4789592
|View full text |Cite
|
Sign up to set email alerts
|

Weighted simultaneous algebraic reconstruction technique for tomosynthesis imaging of objects with high‐attenuation features

Abstract: Results indicate the feasibility of the proposed algorithm to reduce typical tomosynthesis artifacts produced by high-attenuation features. The proposed algorithm assigns weighting coefficients automatically and no segmentation or tissue-classification steps are required. The algorithm can be included into various iterative reconstruction algorithms with an additive updating strategy. It can also be extended to computed tomography case with the complete set of angular data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 35 publications
(29 reference statements)
0
15
0
3
Order By: Relevance
“…mammography Tingberg, 2010). Nevertheless, such diagnostic systems require dedicated equipment and suffer from the presence of background ''clutter'', which comes from high contrast features outside the slice of interest (Levakhina et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…mammography Tingberg, 2010). Nevertheless, such diagnostic systems require dedicated equipment and suffer from the presence of background ''clutter'', which comes from high contrast features outside the slice of interest (Levakhina et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The ideas of the MAR methods for general CT applications may be adapted to DBT, taking into consideration the characteristics of DBT imaging. Several studies have proposed methods for removing metal artifacts for digital tomosynthesis (Chakraborty et al 1984, Badea et al 1998, Claus and Eberhard 2002, Wu et al 2006, Ge et al 2007a, Levakhina et al 2013). An interpolation method was applied along the direction of the blur or in the wavelet domain of the reconstructed image volume (Chakraborty et al 1984, Badea et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…However, the interpolation methods or deblurring technique may introduce new artifacts. Other investigators (Claus and Eberhard 2002, Wu et al 2006, Levakhina et al 2013) identified the PVs that contributed to the artifacts for the reconstructed voxels in the artifact region and assigned different weights to different PVs during the reconstruction, with less or zero weight to the identified affected PVs. With the weighting method, if the affected rays in some PVs are excluded (zero weight) from the reconstruction, the voxels inside the artifact region will obtain unequal number of PV updating compared to the voxels outside the artifact region, potentially causing discontinuous changes in the gray levels inside and outside the artifact region in the reconstructed volume.…”
Section: Introductionmentioning
confidence: 99%
“…Devido a utilização 1.2. Objetivos de um feixe cônico e uma baixa amostragem no domínio da frequência dos sistemas de tomossíntese, os algoritmos de BP e FBP, quando aplicados, introduzem artefatos de objetos fora do foco em imagens que estão em foco no processo de reconstrução (LEVAKHINA et al, 2013;BORGES et al, 2017b). Já os métodos iterativos são capazes de agregar no processo de reconstrução o modelamento físico do sistema em geral, além da possibilidade de incluir restrições à convergência do método a partir de conhecimentos a priori (XU et al, 2015;LEVAKHINA et al, 2013).…”
Section: Motivaçãounclassified
“…Informações a priori como a similaridade dos pixels e a morfologia da imagem foram incorporadas na reconstrução no trabalho de Xu et al (2015). A redução de artefatos de alta atenuação foi incorporada em um algoritmo iterativo, demonstrada no trabalho de Levakhina et al (2013). A correlação do ruído e o respectivo borramento nos detectores indiretos foram estudados por Zheng, Fessler e Chan (2018).…”
Section: Motivaçãounclassified